A case report of inappropriate inhibition of ventricular pacing due to a unique pacemaker electrogram storage feature. Issue 3 (20th March 2021) - Khan, Habib R; Chan, William K; Kanawati, Juliana; Yee, Raymond
Abstract: Background: Modern permanent pacemakers (PPMs) have individual features designed to identify cardiac rhythm abnormalities and improve their performance. Inappropriate pacing inhibition may be an undesired outcome from these features and cause symptoms in patients who require frequent pacing, leading to dizziness, and syncope. Inappropriate inhibition can be difficult to identify in circumstances that are intermittent and difficult to reproduce. Case summary: A 57-year-old female underwent a mitral valve replacement (MVR) for severe mitral stenosis. One month following MVR, she presented with symptomatic third-degree atrioventricular block, and a dual-chamber PPM (Advisa™, Medtronic, Minneapolis, USA) was implanted and programmed DDD 50–130 b.p.m. At the 3-month follow-up, she reported frequent episodes of lightheadedness. She was found to have intermittent ventricular pacing inhibition on a 48-h Holter monitor due to an internal function of the Advisa™ series of PPMs that attempts to store an electrogram (EGM) every 1 h and 30 s. During the EGM storage, an amplified signal from the storage capacitor can result in oversensing by the ventricular channel and inappropriate pacing inhibition. Discussion: To rectify the issue, the ventricular lead sensitivity value was increased from 0.9 mV to 1.2 mV. No instances of inappropriate ventricular pacing inhibition were noted on follow-up. To our knowledge, this is a rare case of inappropriate ventricular pacing inhibition caused by a combination of PPM self-adjusting sensitivity algorithm and oversensing every 1 h and 30 s from an amplified storage capacitor. Physicians should be aware of this possible complication and differentiate it from device or lead malfunction.